The impact of inoculation with the inactivated COVID-19 vaccine on the outcomes of in vitro fertilization and embryo transfer: a cohort study of 1,258 women from Sichuan, China - Wei, Jia-jing; Qiu, Yu; Leng, Mei; Chen, Fu-rui; Liang, Mei-yu; Deng, Xi; Ma, Rong-ning; Hei, Jing; Li-Ling, Jesse; Gong, Yan (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to assess the impact of inoculation with the inactivated coronavirus disease 2019 (COVID-19) vaccine on the outcomes of in vitro fertilization and embryo transfer (IVF-ET).MethodsFrom January 2021 to December 2022, patients undergoing their first cycle of IVF-ET at the Reproductive Medicine Center of Sichuan Provincial Women’s and Children’s Hospital were prospectively enrolled. Based on inoculation with inactivated COVID-19 vaccines before ovarian stimulation (OS) by a gonadotrophin-releasing hormone (GnRH) antagonist or agonist protocol, the patients were divided into the vaccinated group (n = 713) and the unvaccinated group (n = 545). The vaccinated group were sub-grouped based on the dose of inoculation (single dose, n = 74; double dose, n = 275; and triple dose, n = 126) and the interval between the first inoculation and OS (<3 months, n = 65; 3–6 months, n = 123; and >6 months, n = 287).ResultsThe rates of mature oocytes, normal fertilization, cleavage embryo, high-quality cleavage embryo, blastocysts, and high-quality blastocysts were not significantly different between the vaccinated and unvaccinated groups (p > 0.05). For fresh embryo transfer, the implantation rate (IR), the clinical pregnancy rate (CPR), the live birth rate (LBR), the gestational age at delivery, and the birth weight of infants were not significantly different between the two groups (p > 0.05). The IR, CPR, LBR, and birth weight of infants were not significantly different for both the dose and interval subgroups (p > 0.05).ConclusionInactivated COVID-19 vaccines may not affect the outcomes of IVF-ET.